Sex-related immunity: could Toll-like receptors be the answer in acute inflammatory response? - Popotas, Alexandros; Casimir, Georges Jacques; Corazza, Francis; Lefèvre, Nicolas (Frontiers in Immunology, 2024)
An increasing number of studies have highlighted the existence of a sex-specific immune response, wherein men experience a worse prognosis in cases of acute inflammatory diseases. Initially, this sex-dependent inflammatory response was attributed to the influence of sex hormones. However, a growing body of evidence has shifted the focus toward the influence of chromosomes rather than sex hormones in shaping these inflammatory sex disparities. Notably, certain pattern recognition receptors, such as Toll-like receptors (TLRs), and their associated immune pathways have been implicated in driving the sex-specific immune response. These receptors are encoded by genes located on the X chromosome. TLRs are pivotal components of the innate immune system, playing crucial roles in responding to infectious diseases, including bacterial and viral pathogens, as well as trauma-related conditions. Importantly, the TLR-mediated inflammatory responses, as indicated by the production of specific proteins and cytokines, exhibit discernible sex-dependent patterns. In this review, we delve into the subject of sex bias in TLR activation and explore its clinical implications relatively to both the X chromosome and the hormonal environment. The overarching objective is to enhance our understanding of the fundamental mechanisms underlying these sex differences.